Hostile Takeovers in India: New Prospects, Challenges and Regulatory Opportunities: Exploring the landscape of hostile takeovers and regulation in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
“In recent years, the tender offer takeover has been praised and damned with a ferocity suggesting that the survival of capitalism is at stake. The truth, as in most disputes with substantial metaphysical content, is more prosaic.” F. M. Scherer, Journal of Economic Perspectives, winter 1988, pg, 69.